Formulation and in-vitro Evaluation of Oro-dispersible tablets of Indomethacin - Pokhrel, Gopal; Kunwar, Ganga; Rai, Jun Devi; Thapa, Sheela; Dhakal, Sudip; Basnet, Prashant (Nepal Journal of Health Sciences, 2022)
Introduction: Oro-dispersible tablets are rapidly dissolved in saliva without the need for water and are beneficial for renal impaired, bedridden and psychiatric patients. Objective: The study aimed to formulate oro-dispersible tablets of indomethacin with reduced adverse effects, better patient compliance, faster action, and convenience for patients. Methods: Oro-dispersible tablets of indomethacin were prepared using three different super disintegrants; crospovidone, croscarmellose sodium and sodium starch glycolate with three different concentrations (2.5%, 5.2%, and 7.7%) by direct compression method. The prepared tablets were evaluated for pre and post-compression parameters including bulk density, tapped density, compressibility index, angle of repose, Hausner’s ratio, hardness, friability, wetting time, in vitro disintegration time, and in vitro drug release. Results: The percentage of drug released in 5 minutes of all formulations of Oro-dispersible tablets of Indomethacin was found to be 74.36% to 80.16% and the percentage of drug released in 10 minutes was 96.18% to 100%. All formulations showed disintegration time in the range of 19-78 seconds. The tablets prepared with 7.7% crospovidone (F6) shows faster disintegration (19 seconds) as compared to tablets prepared with sodium starch glycolate and croscarmellose sodium. The in-vitro dissolution studies showed that tablets of formulations batch containing 7.7% crospovidone releases 100% of the drug after 10 minutes which was fast released as compared to sodium starch glycolate and croscarmellose sodium. Conclusions: Oro-dispersible tablets of indomethacin prepared with crospovidone showed better disintegration time and dissolution profile as compared to other superdisintegrants.